2017
DOI: 10.1016/j.ijheatmasstransfer.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of an aerosol source in forced ventilation through prior identification of a convolutive model

Abstract: This article presents a method for estimating the time dependent generation rate of an aerosol source starting from a transient concentration signal measured at a distant point. The method is made up of two distinct steps: a calibration phase, followed by an estimation phase. The calibration phase consists in identifying a transfer function (termed "impedance") between a known source (the "calibration source") and its measured concentration response. In the second step the unknown source generation rate, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In a previous study, it was found that increasing the calculation time step properly could reduce the measurement noise effect. However, decreasing the calculation time step would ensure a higher resolution for the inverse source strength (Wang and You 2015;Chata et al 2017). Therefore, the optimal calculation time step should balance the inverse accuracy and resolution.…”
Section: Effects Of Time Resolutionsmentioning
confidence: 99%
“…In a previous study, it was found that increasing the calculation time step properly could reduce the measurement noise effect. However, decreasing the calculation time step would ensure a higher resolution for the inverse source strength (Wang and You 2015;Chata et al 2017). Therefore, the optimal calculation time step should balance the inverse accuracy and resolution.…”
Section: Effects Of Time Resolutionsmentioning
confidence: 99%
“…The convolution product (1b) can be defined in two different ways, using its commutative property [23] : ). This can be put under a column vector/matrix form:…”
Section: Impulse Response Identification and Principle Of A Thermal Fouling Detectormentioning
confidence: 99%